The Consociation and Promoting Citizenship for Minorities in Iraq - Azo Hamdo, Mahmud (Journal of Duhok University, 2019)
The subject of citizenship regards of the most important challenges that the modern state especially , in the societies of pluralism and variety that consist of several ethnics and seets, so , the blostering of existing of minorities through blostering of its rights that confirming the citizenship through Consociational Democracy able and the availability of its application in peace , so as to , maintaining and containment these minorities to build Iraqi citizenship containing all Iraqis social component.